Impact of Gross Domestic Product on the Growth of Bond Markets in Kenya - Amenya, Linet Moraa; Muturi, Willy Muturi; Oluoch, Oluoch Oluoch; Kagiri , Assumpta Kagiri (International Journal of Finance, 2022)
Purpose: Bond markets are an example of financial markets that are very essential in promoting greater economic efficiency by channeling funds from savers to investors. This study investigated the influence of gross domestic product on growth of bond market in Kenya. The study further examined the moderating effect of diaspora remittance on the relationship between gross domestic product and the growth of bond market in Kenya. Methodology: Secondary data was obtained from the CBK, KNBS and NSE and covered a period of 20 years. Time series regression analysis was used in the study. The study employed descriptive research design. Findings: The study established that the gross domestic product had a major effect on the growth of bond market for the period of study. The study findings revealed that the GDP had a strong positive influence on the growth of bond markets. After moderation the effect improved more with the significance p-value. The study concluded that there was a positive statistically significant effect of GDP on bond market growth in Kenya. Unique Contribution to Theory, Policy and Practice: The study recommended that the capital market authority as a policy maker should enhance policies that promote investment in the bond market. Further studies should also be carried out incorporating other macroeconomic variables not included in this study. Finally, the study also recommended that CBK should ensure that it improves on measures that control the GDP and diaspora remittance as they influence the growth of bond market.